PENINGKATAN MUTU STANDAR ISI DAN STANDAR PROSES PENDIDIKAN DENGAN MENDESAIN PEMBELAJARAN BERBASIS INKUIRI MELALUI WORKSHOP DAN PENDAMPINGAN - Wahyuni, Sri (Universitas Hamzanwadi, 2019)
This study is aiming at describing the activities committed by teachers to improve the content standard of national education by designing the inquiry based learning. Method applied in this study is descriptive qualitative. The subjects of the study are the teachers of SMAN 2 Selong. To obtain the preliminary data, this study utilizes the analysis toward the result of the evaluation of education quality reported by the institution of quality education assurance so called LPMP (Lembaga Penjaminan Mutu Pendidikan) at Province of West Nusa Tenggara. For attaining the qualitative data, the author uses instrument of observation during the workshop and supervision. The result of the study shows that there is an improvement of the quality in the planning the design of teaching and learning as well as implementing the program. It is recommended that teachers should be more active in trying to improve the quality of the administration equipment of teaching in order to get the better result.